Diagnosing a Gastric Submucosal Tumor Using Jumbo Biopsy “Unroofing” Technique: A Case Report and Review of the Literature - Sakshi Kapur; Pradeep Mahal; Levin Miles; Adnan Hussain (Case Reports in Oncological Medicine)
We report a case of a 40-year-old female who presented with dyspeptic symptoms for six months. Upper GI endoscopy revealed a submucosal nodule in gastric antrum. Using “jumbo biopsy unroofing technique” we were able to get adequate tissue for analysis. Histopathology revealed a type III gastric carcinoid. Patient was treated with laparoscopic distal subtotal gastrectomy with Roux-en-Y reconstruction and partial omentectomy. Although there was no evidence of metastasis on initial presentation, eighteen months later, patient was found to have multiple metastatic lesions in her liver. Patient’s lesions were treated with intra-arterial (hepatic artery) Yttrium-90.